Potential Activity, Size, and Structure of Sulfate-Reducing Microbial Communities in an Exposed, Grazed and a Sheltered, Non-Grazed Mangrove Stand at the Red Sea Coast - Balk, Melike; Keuskamp, Joost A.; Laanbroek, Hendrikus J. (Frontiers in Microbiology, 2015)
After oxygen, sulfate is the most important oxidant for the oxidation of organic matter in mangrove forest soils. As sulfate reducers are poor competitors for common electron donors, their relative success depends mostly on the surplus of carbon that is left by aerobic organisms due to oxygen depletion. We therefore hypothesized that sulfate-cycling in mangrove soils is influenced by the size of net primary production, and hence negatively affected by mangrove degradation and exploitation, as well as by carbon-exporting waves. To test this, we compared quantitative and qualitative traits of sulfate-reducing communities in two Saudi-Arabian mangrove stands near Jeddah, where co-occurring differences in camel-grazing pressure and tidal exposure led to a markedly different stand height and hence primary production. Potential sulfate reduction rates measured in anoxic flow-through reactors in the absence and presence of additional carbon sources were significantly higher in the samples from the non-grazed site. Near the surface (0-2cm depth), numbers of dsrB gene copies and culturable cells also tended to be higher in the non-grazed sites, while these differences were not detected in the sub-surface (4-6 cm depth). It was concluded that sulfate-reducing microbes at the surface were indeed repressed at the low-productive site as could be expected from our hypothesis. At both sites, sulfate reduction rates as well as numbers of the dsrB gene copies and viable cells increased with depth suggesting repression of sulfate reduction near the surface in both irrespective of production level. Additionally, sequence analysis of DNA bands obtained from DGGE gels based on the dsrB gene, showed a clear difference in dominance of sulfate-reducing genera belonging to the Deltaproteobacteria and the Firmicutes between sampling sites and depths.